2015
DOI: 10.7567/jjap.54.06fj02
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial synthesis of BaTiO3–Bi(Mg2/3Nb1/3)O3thin-films for high-temperature capacitors

Abstract: Combinatorial thin-film of (1−x)[BaTiO3]–x[Bi(Mg2/3Nb1/3)O3] — (BT–BMN) was grown on Pt/Ti/SiO2/Si, using pulse laser deposition (PLD) method, by ablating stoichiometric and Bi-10 wt % enriched targets to optimize the Bi content. X-ray photoelectron spectroscopy analysis revealed a linear Bi composition spread. As-deposited films post-annealed at high-temperatures, under oxygen atmosphere, turned into crystalline state. The crystallinity, characterized by X-ray diffraction, is better towards Bi-enriched region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Prior to BT-BMN growth, BT-BMN (50 nm) and later SRO were deposited onto substrates at 540 °C at an O2 partial pressure of 0.13 Pa to prevent intermixing at the BT-BMN/STO interface and epitaxial growth of BT-BMN. In addition, our previous work revealed that SRO insertion improved the thermal stability of the dielectric properties of BT-BMN films and that polycrystalline structures reduced the surface roughness and leakage current (12,22).…”
Section: Experimental Methodsmentioning
confidence: 95%
“…Prior to BT-BMN growth, BT-BMN (50 nm) and later SRO were deposited onto substrates at 540 °C at an O2 partial pressure of 0.13 Pa to prevent intermixing at the BT-BMN/STO interface and epitaxial growth of BT-BMN. In addition, our previous work revealed that SRO insertion improved the thermal stability of the dielectric properties of BT-BMN films and that polycrystalline structures reduced the surface roughness and leakage current (12,22).…”
Section: Experimental Methodsmentioning
confidence: 95%
“…The BT-BMN films were grown on 0.5 wt % Nb doped (100) SrTiO 3 (STO) single-crystal substrates by pulsed laser deposition. On the basis of the temperature dependence of the dielectric constant results of bulk ceramics and our previous results, 12,19) a sintered ceramic target with a composition of 0.6[BaTiO 3 ]-0.4[Bi(Mg 2=3 Nb 1=3 )O 3 ] enriched with 10 wt % Bi 2 O 3 was prepared through the solidstate reaction route and preinstalled on the rotating stage of the deposition chamber. The target was ablated by a KrF excimer laser with a wavelength of 248 nm, a repetition rate of 10 Hz, and an energy density of 1.5 J=cm 2 at room temperature with oxygen, containing 4% ozone, with a partial pressure of 20 Pa.…”
Section: Methodsmentioning
confidence: 99%
“…The combinatorial technique is a well-known method for accelerating the screening of each synthesis process and the characteristic properties of complicated doping materials, such as superconductive materials, 2,12) phosphor materials, 13) shape memory alloys, 14,15) magnetic materials, 6,16) and dielectric materials. [17][18][19][20] The combinatorial method enables the integration of functional films with different chemical compositions on a single-chip substrate and the quick evaluation of the characteristic properties that are dependent on the chemical composition of the material with the desired functionality. By combining it with pulsed laser deposition (PLD), many singlecrystal films can be synthesized simultaneously and systematically evaluated to obtain a large amount of high-quality experimental data originating from single-crystal films.…”
Section: Introductionmentioning
confidence: 99%